Clumping and X-rays in cooler B supergiant stars - Bernini Peron, Matheus; Marcolino, W. L. F.; Sander, Andreas A. C.; Bouret, J.-C.; Ramachandran, Varsha; Saling, J.; Schneider, Fabian; Oskinova, L. M.; Najarro, F. (Astronomy and astrophysics, 2023)
Methods. We determined photospheric and wind parameters via quantitative spectroscopy using atmosphere models computed with CMFGEN and PoWR. These models were compared to high-resolution UV and optical spectra of four BSGs: HD206165, HD198478, HD53138, and HD164353. We further employed GENEC and MESA tracks to study the evolutionary status of our sample. - Results. When including both clumping and X-rays, we obtained a good agreement between synthetic and observed spectra for our sample stars. For the first time, we reproduced key wind lines in the UV, where previous studies were unsuccessful. To model the UV spectra, we require a moderately clumped wind ( fV∞ ≳ 0.5). We also infer a relative X-ray luminosity of about 10−7.5 to 10−8, which is lower than the typical ratio of 10−7. Moreover, we find a possible mismatch between evolutionary mass predictions and the derived spectroscopic masses, which deserves deeper investigation as this might relate to the mass-discrepancy problem present in other types of OB stars. - Conclusions. Our results provide direct spectroscopic evidence that both X-rays and clumping need to be taken into account to describe the winds of cool BSGs. However, their winds seem to be much less structured than in earlier OB-type stars. Our findings are in line with observational X-rays and clumping constraints as well as recent hydrodynamical simulations. The evolutionary status of BSGs seems to be diverse with some objects potentially being post-red supergiants or merger products. The obtained wind parameters provide evidence for a moderate increase of the mass-loss rate around the bi-stability jump.
Gesehen am 31.03.2025
Online verfügbar: 5 September 2023